Empirical investigation on the relationship between exports and economic growth in selected LDCs country groups (1988-2018) - Khalil Ghazi Hassan (Universitas Islam Indonesia, 2020)
This study aims to investigate the export-led growth hypothesis for two developing country groups i.e. the Middle East and North African (MENA), and South Asian (SA) countries. The study uses time-series data for the period of (1990-2018) based on the unit root, cointegration, error correction modelling, and Granger causality tests. Findings/originality: The results found a long-run cointegration, but no evidence for significant relations between the variables was confirmed. Furthermore, there is no Granger causality between economic growth and exports in the two directions for the MENA countries. But for the SA countries, we note a unidirectional causality from economic growth to exports, i.e. the growth in both country groups was not driven by an export-led growth strategy. This implies that exports aren’t the cause of output growth, and Accordingly, looking for alternative factors of growth in the countries concerned can be suggested.